EFFECTS OF ORGANIC MANURE ON GROWTH PERFORMANCE OF Azadirachta indica (A. JUSS) SEEDLINGS DURING EARLY GROWTH IN THE NURSERY (FUDMA JOURNAL OF SCIENCES, 2023)
Seedling production in the forest nursery is very inevitable; therefore, there is need to examine fertilizer on seedlings growth in preparation for plantation in the growing season. A research investigated the effect of poultry manure treatment at different levels on the growth and early performance of Azadirachta indica (Neem) seedlings. Soils used for the experiment were collected from study area. The seeds collected on the ground were distributed and planted at the same proportion of sand but different ratio of poultry manure. Experiment had four (4) treatments in which each them had the same proportion of river and top soil but different ratio of poultry manure:T1(1:1:2), T2(1:1:3),T3(1:1:4) and T4(1:1) control respectively. Complete Randomized Design (CRD) was used for this research with four (4) treatments and five (5) replications making twenty (20) samples all together. The growth parameters measured include: number of leaves, stemdiameter and growth height. Analysis of variance showed that there were no significant difference (p
Keywords: Organic manure, early performance, Azadirachta indica, nursery stage and effect